Optimization of Player Experience and Enemy AI using A* Algorithm in Game - Arifudin, Dani; Fransjaya, Michael; El Fakhry , Yusif; Syahrizaldy, Hikmalul A’la (Politeknik Ganesha Medan, 2025)
The gaming industry is rapidly evolving, where engaging and challenging gameplay has become a key factor in a game's success. Effective enemy intelligence can enhance challenges and enrich the player experience. This study aims to improve the player experience and enemy intelligence in the game Galang the EcoRescue through the implementation of the A-star (A*) algorithm. A* is a pathfinding algorithm that uses distance estimation to find the shortest path to a target by utilizing a heuristic function. This game was developed using the Unity Engine, with the implementation of the A* algorithm to determine enemy movements and adapt their behavior according to the game’s situation. Testing was conducted to ensure improvements in both the player experience and enemy intelligence. The results of the study show that the A* algorithm successfully enhanced enemy intelligence by creating more realistic and adaptive movements in response to the player, ultimately providing more dynamic challenges and improving overall gameplay quality. This study utilized the Game Development Life Cycle (GDLC) method, covering the stages of initiation, pre-production, production, testing, beta, and release. The A* algorithm has proven to optimize the player experience in Galang the EcoRescue.